Prličevite besedi: stilistički aspekty - Gurkova, Аleksandra (Stylistyka, 2021)
Main topie of this paper is the stylistic structure of the orations of Grigor Prli- chev, which were written and performed by the occasion of different religious ho- lidays or dedicated for the end of the study year at different schools where he was teaching throughout Macedonia.Several specifics are to be taken in consideration: elements of cohesion, different ways of addressing, some syntactic characteristics, use of style figures etc. The intonation used by the author should also be taken in regard, although it can- not be subject to analysis for obvious reasons.One of the most important specifics is the use of lithurgical elements, compari- sons with biblical motives, use of rhetorical questions, ways of addressing the pu- blic with intention of establishing familiarity etc. There is also, freąuent use of developed poetic images, dialogues with a purpose of developing the topie and promotion of the didactic function. This analysis is a contribution to the further study of the composition of the orations of Grigor Prlichev.